2007
DOI: 10.1016/j.mcn.2006.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative suppression of Cav2.1 currents by α12.1 truncations requires the conserved interaction domain for β subunits

Abstract: Episodic ataxia type 2 (EA2) is an autosomal dominant disorder arising from CACNA1A mutations, which commonly predict heterozygous expression of Ca v 2.1 calcium channels with truncated α 1 2.1 pore subunits. We hypothesized that α 1 2.1 truncations in EA2 exert dominantnegative effects on the function of wild-type subunits. Wild-type and truncated α 1 2.1 subunits with fluorescent-protein tags were transiently co-expressed in cells stably expressing Ca v auxiliary β subunits, which facilitate α 1 -subunit fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 67 publications
1
9
1
Order By: Relevance
“…Importantly, ER retention of misfolded proteins can be overcome by lowering culture temperature in mammalian cells (Denning et al, 1992;Morello et al, 2000), as recently reported for EA2 mutants (Jeng et al, 2008). Other data suggest that Ca v 2.1 subunit splice variants might be differentially affected by DIM (Jeng et al, 2006) and that auxiliary subunit expression and stoichiometry may modulate DIM (Arikkath et al, 2002;Raike et al, 2007). Altogether, our data reconcile the apparently controversial data on EA2 mutant dominant activity that appear to be principally attributable to variation in the ER retention and cellular degradative capacity.…”
Section: Casupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, ER retention of misfolded proteins can be overcome by lowering culture temperature in mammalian cells (Denning et al, 1992;Morello et al, 2000), as recently reported for EA2 mutants (Jeng et al, 2008). Other data suggest that Ca v 2.1 subunit splice variants might be differentially affected by DIM (Jeng et al, 2006) and that auxiliary subunit expression and stoichiometry may modulate DIM (Arikkath et al, 2002;Raike et al, 2007). Altogether, our data reconcile the apparently controversial data on EA2 mutant dominant activity that appear to be principally attributable to variation in the ER retention and cellular degradative capacity.…”
Section: Casupporting
confidence: 88%
“…Additionally, it has also been shown that some EA2 mutants exert a dominant-negative effect (Jouvenceau et al, 2001;Page et al, 2004;Jeng et al, 2006). Several mechanisms have been proposed for this effect, including competition of mutant channels for auxiliary subunits and/or the cell trafficking machinery (Arikkath et al, 2002;Cao et al, 2004;Wan et al, 2005;Raike et al, 2007;Jeng et al, 2008) and translational arrest (Page et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A dominant negative effect of EA2 mutant Ca V 2.1 α-subunit on normal protein has been demonstrated by double transfection methods for mutations producing PTCs as well [6,[11][12][13][14]. However, the present results on leaner mice and the similar phenotype of cacna1a null, knockout and knockdown mice [20][21][22] would indicate that also a haploinsufficiency mechanism can cause ataxia.…”
Section: Discussioncontrasting
confidence: 60%
“…EA2 is an early onset, autosomal dominant disorder characterised by attacks of vertigo/ataxia, visual disturbance, dysarthria, interictal cerebellar deficit of extremely variable severity, and cerebellar atrophy; epilepsy has occasionally been described [9,10]. A dominant negative effect of the Ca V 2.1 mutated protein affecting the wild type product, rather than a haploinsufficiency, has been hypothesised [6,[11][12][13][14]. Loss of function mutations of the mouse orthologue of the CACNA1A gene cause recessive neurological phenotypes, in tottering (cacna1a tg ; tg), leaner (cacna1a tg-la ; tg-la), rocker (cacna1a rkr ) and rolling Nagoya (cacna1a tg-rol ) mice [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A clear dominant negative effect of EA2 mutants was revealed by coexpression of several EA2 missense and truncation mutants with WT human Ca V 2.1 channels in mammalian cells [53,84,105]. The coexpression led to ER retention and reduction of membrane expression of the WT Ca V 2.1 channel, resulting in a reduced Ca 2+ current [53,84]; both the impaired localization and reduced Ca 2+ current were rescued if the cells were incubated for a few days at 27°C [53].…”
Section: Functional Consequences Of Ea2 Mutations On Recombinant Humamentioning
confidence: 99%